2016
DOI: 10.1002/art.39475
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Responsiveness to Treatment of Lung Abnormalities on Chest Computed Tomography in Patients With Microscopic Polyangiitis: A Multicenter, Longitudinal, Retrospective Study of One Hundred Fifty Consecutive Hospital‐Based Japanese Patients

Abstract: Objective. To determine the prevalence of lung abnormalities on chest computed tomography (CT) in patients with microscopic polyangiitis (MPA), to assess the responsiveness of such abnormalities to initial treatment, and to assess associations between these abnormalities and patient and disease characteristics and mortality.Methods. We retrospectively identified 167 consecutive hospital-based patients with MPA in 3 hospitals in Japan. We longitudinally collected clinical information for 150 of these patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 42 publications
5
61
2
9
Order By: Relevance
“…In addition, some airway abnormalities were seen in 66% of patients, described as bronchiolitis (55%), bronchial wall thickening (44%), and bronchiectasis (32%). Pleural lesions were also reported in 53% of cases and described as pleural thickening in 34% and effusion in 26% of cases [52]. Another series of 40 patients reported that pulmonary complaints and infiltrates were present in 80 and 92% of patients, respectively [53].…”
Section: Presentation and Diagnosismentioning
confidence: 96%
“…In addition, some airway abnormalities were seen in 66% of patients, described as bronchiolitis (55%), bronchial wall thickening (44%), and bronchiectasis (32%). Pleural lesions were also reported in 53% of cases and described as pleural thickening in 34% and effusion in 26% of cases [52]. Another series of 40 patients reported that pulmonary complaints and infiltrates were present in 80 and 92% of patients, respectively [53].…”
Section: Presentation and Diagnosismentioning
confidence: 96%
“…Interstitial lung lesions are a frequent finding in radiologic studies of ANCA-V patients [64]. In a cohort of 150 MPA individuals, CT images obtained before treatment showed that 97% presented at least one lung abnormality, including interstitial lung changes in 66% [64].…”
Section: Imagingmentioning
confidence: 99%
“…Similarly, in another study that included 62 MPO-ANCA cases (51 with MPA), 82% had an abnormal CT scan, 94% of which displayed findings suggestive of interstitial involvement [65]. Most of these interstitial lesions are non-specific and only a small number of patients will actually show a CT pattern corresponding to some specific idiopathic interstitial pneumonia, such as usual interstitial pneumonia (UIP) or non-specific interstitial pneumonia (NSIP) [64,66]. …”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations